The science and engineering of materials - Askeland, Donald R. (Thomson, 2006)
This text provides an understanding of the relationship between structure, processing, and properties of materials. By selecting the appropriate topics from this wealth of material, instructors can emphasize metals, provide a general overview of materials, concentrate on mechanical behavior, or focus on physical properties. Since the book has more material than is needed for a one-semester course, students will also have a useful reference for subsequent courses in manufacturing, materials, design, or materials selection.